Post-harvest cleaning, sanitization, and microbial monitoring of soilless nutrient delivery systems for sustainable space crop production - Curry, Aaron B.; Spern, Cory J.; Khodadad, Christina L. M.; Hummerick, Mary E.; Spencer, LaShelle E.; Torres, Jacob; Finn, J. Riley; Gooden, Jennifer L.; Monje, Oscar (Frontiers in Plant Science, 2024)
Bioregenerative food systems that routinely produce fresh, safe-to-eat crops onboard spacecraft can supplement the nutrition and variety of shelf-stable spaceflight food systems for use during future exploration missions (i.e., low earth orbit, Mars transit, lunar, and Martian habitats). However, current space crop production systems are not yet sustainable because they primarily utilize consumable granular media and, to date, operate like single crop cycle, space biology experiments where root modules are sanitized prior to launch and discarded after each grow-out. Moreover, real-time detection of the cleanliness of crops produced in spacecraft is not possible. A significant paradigm shift is needed in the design of future space crop production systems, as they transition from operating as single grow-out space biology experiments to becoming sustainable over multiple cropping cycles. Soilless nutrient delivery systems have been used to demonstrate post-harvest sanitization and inflight microbial monitoring technologies to enable sequential cropping cycles in spacecraft. Post-harvest cleaning and sanitization prevent the buildup of biofilms and ensure a favorable environment for seedling establishment of the next crop. Inflight microbial monitoring of food and watering systems ensures food safety in spaceflight food systems. A sanitization protocol, heat sterilization at 60°C for 1 h, and soaking for 12 h in 1% hydrogen peroxide, developed in this study, was compared against a standard hydroponic sanitization protocol during five consecutive crop cycles. Each cropping cycle included protocols for the cultivation of a crop to maturity, followed by post-harvest cleaning and inflight microbial monitoring. Microbial sampling of nutrient solution reservoirs, root modules, and plants demonstrated that the sanitization protocol could be used to grow safe-to-eat produce during multiple crop cycles. The cleanliness of the reservoir and root module surfaces measured with aerobic plate counts was verified in near real time using a qPCR-based inflight microbial monitoring protocol. Post-harvest sanitization and inflight microbial monitoring are expected to significantly transform the design of sustainable bioregenerative food and life support systems for future exploration missions beyond low earth orbit (LEO).